2017
DOI: 10.4172/2151-6219.1000326
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Tax Payments and Corporate Social Responsibility: Complements or Substitutes? Empirical Evidence from Europe

Abstract: Recent empirical studies find mixed evidence on the relation between corporate social responsibility and corporate tax payments. We investigate for a European sample whether the two constructs act as substitutes or complements. We analyse the relation using a linear unobserved effects panel model. Our findings suggest that corporate social responsibility and corporate tax payments act as substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…In line with the view of those who do not believe that the principles of CSR are real and adequately addressed in management practices, Preuß and Björn [35] found that CSR is negatively associated with tax payments and they suggested that corporate tax payments and CSR from European public companies act as substitutes. These authors concluded that corporate tax payments may not be viewed as part of CSR.…”
Section: Theoretical and Practical Issues On Social Responsibility Ethics And Tax Managementmentioning
confidence: 75%
“…In line with the view of those who do not believe that the principles of CSR are real and adequately addressed in management practices, Preuß and Björn [35] found that CSR is negatively associated with tax payments and they suggested that corporate tax payments and CSR from European public companies act as substitutes. These authors concluded that corporate tax payments may not be viewed as part of CSR.…”
Section: Theoretical and Practical Issues On Social Responsibility Ethics And Tax Managementmentioning
confidence: 75%
“…Golden Tax Project III enhanced tax administration and reduced opportunities for tax avoidance, thus increasing the tax and cost burden on firms [4][5][6]. In addition, studies have pointed out that corporate tax payments and corporate social responsibility are substitutes for each other and that degree of corporate tax avoidance is significantly and positively related with ESG performance [7,8]. This suggests that taxation may increase cost pressure on firms and reduce their willingness to engage in ESG activities.…”
Section: Introductionmentioning
confidence: 99%